L’umanità al varco. L’intelligenza artificiale può essere lo “scrigno” delle verità sull’essere umano - Nausica Lucia Guglielmo (Democrazia e Diritti Sociali)
When observing contemporary society, one cannot fail to notice how pressing man’s desire to ‘domesticate’ his own existence is wanting to make it completely similar to a linear and controlled process. In this sense, man seems to manifest the will to homologate his humanity to the ‘schematism’ produced by the mechanisms on which artificial intelligence is based. The legal sector seems to lend itself well to this type of reasoning, especially if attention is paid to the application of artificial intelligence in the process, which would guarantee an impeccable and perfectly functioning procedure in a system in which the human being and the machine can mutually influence each other and derive mutual benefits. But, in this system, even if perfect, it would not be possible to totally exclude the error that artificial intelligence may be responsible for. And what if, in such a context, it was precisely the error determined by artificial intelligence that presented man with his truth as a human being?